A Study on Mental Stress among B Ed Students - Hemalatha, M Mary; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
The nobility of the teaching profession has been extolled in almost every community around the world. Teachers play a pivotal role as the ‘future builders’ of our country and the respect they command in the general public is unparalleled. The stress response is the body’s way of protecting the person. The stress response helps the person to first of all focus completely on one’s safety and more precisely the physical safety. A student who is writing his examination, despite having prepared for it for years, if suddenly finds a snake slithering under his chair may immediately jump out and break all the decorum of examination hall. Nevertheless, stress response is not just limited to physical danger. In the highly evolved human lifestyle of today, the psychological danger of being humiliated in front of others, losing a job and thus being threatened of loss of status quo, the possibility of failing in a job interview, the probability of rejection in a relationship – all these can trigger the stress response. The term ‘mental stress’ is medically associated with pathophysiologic responses such as insomnia, bowel disorders and headaches. The extent of such physiological effects or conditions are based on the severity of the stressor or the strength of the coping mechanism of the individual. A study shows the relationship between cardiac event and 22% cohort of mentally stressful environment. Normative- Survey research is directed towards ascertaining the prevailing conditions. It seeks to answer the question, "What are the real facts with regards to the existing conditions". The normative-survey approach is appropriate wherever the objects of any class vary among themselves and one is interested in knowing the extent to which different condition are obtained among these objects. Stratified Clustering sample of 300 students of B.Ed., students were selected from Chennai. The study does not argue that there is no mental stress among the B.Ed., students; it only records that the mental stress is at an average level at this point of time. The key learning points of this study project is quite valid and categorical. The investigator truly believes that if these learning points and some the recommendations are implemented, then we can systematically equip our students to handle mental stress in a productive way. How to cite this article: Hemalatha MM, Selvakumar YS. A Study on Mental Stress among B.Ed Students. J Adv Res Eng & Edu 2022; 7(2): 14-16. DOI: https://doi.org/10.24321/2456.4370.202210